Analisis Rasio Keuangan Terhadap Return Saham Dengan Menjadikan Total Assets Turnover Sebagai Variabel Pemoderasi Perusahaan Sektor Real Estate And Property - Do Bagus, Marwah Khairunnisa; Mulyadi, JMV; Djadaang, Syahril (Institut Bisnis dan Informatika Kesatuan, 2018)
This study aims to analyze and examine debt to equity ratio (DER), return on assets (ROA) to stock return and total asset turnover (TATO) as a moderating variable in real estate and property firms listed on Indonesia Stock Exchange period 2011 -2015. The population in this study is real estate and property companies listed in Indonesia Stock Exchange (IDX) period 2011-2015. Criteria to this samples are 19 real estate and property companies listed in the Stock Exchange during a periods 2011 until 2015, thus we get the total amount of data during the period is 95. From the results of hypothesis test by moderating regression analysis it can be concluded that: return on assets have a positive and significant effect on stock return, and the influx of total assets turnover significantly moderate the effect of return on assets on stock returns, The debt to equity ratio has a negative and not significant to stock return, and the inclusion of total assets turnover not able to significant moderate influence debt to equity ratio to stock return.